“I've learned a lot from watching Netflix series with LGBTQ issues in it”: An Audience Study on How Netflix LGBTQ+ Series Expand Perspectives and Cultivate Awareness - Trisnawati, Ririn Kurnia; Sutikno, Eka Ugi; Agustina, Mia Fitria; Difayana, Alifia Gian; Amanda, Naura Fitri; Noorashid, Najib (Universitas Ahmad Dahlan, 2025)
This study examines how Indonesian audiences respond to LGBTQ+ narratives in Netflix series such as Feel Good (2020), Heartstopper (2022), and Glamorous (2023) through Stuart Hall's Audience Reception Theory. Employing a qualitative approach with 29 participants, it explores how these series influence viewers' knowledge, and awareness, particularly in relation to cultural and societal norms. The findings indicate that these narratives contribute to audience understanding across five key areas: LGBTQ+ identity and experiences, cultural and societal insights, moral lessons, challenges faced by LGBTQ+ individuals, and critical perspectives on representation. Additionally, the study identifies four distinct awareness categories: recognizing LGBTQ+ individuals as human beings, understanding their experiences, acknowledging diverse gender identities, and recognizing the media’s role in shaping perceptions. These results suggest that exposure to LGBTQ+ content in streaming media can promote empathy, broaden perspectives, and challenge existing biases. By highlighting the informative and awareness-raising potential of these series, the study underscores the role of media in shaping public discourse and social attitudes toward gender and sexuality, ultimately contributing to a growing recognition of diverse identities within Indonesian society.